EFL STUDENTS' MOTIVATION IN MASTERING ENGLISH GRAMMAR THROUGH TEAM GAME TOURNAMENT (TGT) - Nurul Hasanah (JURNAL EDUKASI NONFORMAL, 2021)
The objective of the research was to find out whether the students of Accounting for Islamic Financial Institutions IAIN Parepare are motivated in learning English Grammar through Team Game Tournament (TGT). The researcher applied descriptive method and using both offline and online quizzes as the game in the learning process. The population was the students of Accounting for Islamic Financial Institutions at fourth semester. This research applied cluster random sampling by taking one class as the sample, that was the fourth semester students of Accounting for Islamic Financial Institutions. The sample consisted of 26 students. The data were collected through questionnaire and supported by observation checklist. The result of this research showed that the fourth semester students of Accounting for Islamic Financial Institutions IAIN Parepare were highly motivated in learning English through Team Game Tournament (TGT).